Planning the assessment of learning outcomes in educational programs design - A. I. Chuchalin; A. V. Epikhin; E. A. Muratova (Высшее образование в России, 2022)
The paper is focused on the upgraded technology for educational programs design considering the assessment of learning outcomes immediately after forming the initial datafor designing the program, exactly the required competences of the graduates. Within the two-stage life cycle model of the educational program on the stage of learning outcomes planning the methods, indicators and criteria are defined to assess the competences acquired by the students. The key definitions used while implementing the above mentioned procedures are specified; and their interconnections are described. The recommendations for learningoutcomes assessment are provided, which are aimed at assessment of correlation betweenengineering educational programs learning outcomes assessment and the requirements of federal educational standards along with the international standards for engineering education.